Experimental and modeling study of chemical-based strategies for mitigating dust formation in fusion reactors. (26th February 2019) - Koroglu, Batikan; Mehl, Marco; Crowhurst, Jonathan C; Zaug, Joseph M; Rose, Timothy P; Radousky, Harry B; Armstrong, Michael R
Abstract: We studied carbon/hydrogen/oxygen chemical kinetics at time scales and thermal conditions relevant to fusion energy applications using a custom-built plasma flow reactor to investigate chemical-based strategies for eliminating carbon dust formation in fusion reactors. Acetylene and oxygen gases under varying conditions of initial concentrations are injected into an inductively coupled argon plasma where complete molecular dissociation occurs. The evolution of chemical species is investigated along the plasma flow reactor as a function of temperature and residence time. Atomized species of C, H, and O cool from 5000 to 1000 K within 30 ms at atmospheric pressures. We employed optical emission and infrared absorption spectroscopy to measure the reaction intermediates (e.g. C2 ) and products (e.g. C2 H2 ). Chemical equilibrium models are inadequate to describe the evolution of carbon molecular products, and thus a chemical kinetics model is developed. In both experiments and kinetic modeling, we find that the addition of oxygen in 1:1 proportion to carbon strongly favors the formation of CO, preventing the formation of acetylene (an important soot precursor) in less than 10 milliseconds. The kinetics model is also used to perform reaction sensitivity and a rate of production analyzes to identify the rate determining steps and the major chemical pathways that control the acetylene production/consumption. The results demonstrate the feasibility of chemical-based strategies for eliminating the formation of carbonaceous particles in fusion energy reactors.